Wizualizacja wyników jakościowych badań koniunktury gospodarczej - Kowalewski, Grzegorz (Visualization of Results of Business Tendency Surveys, 2009)
By using answer balance in describing the economic conjuncture one does not take into consideration the full information about the structure of an answer to given question. This comes from the belief that the full information is not of a great importance. However, such approach "glues together" the cases of different structures of answers. The author believes that one cannot give up on the full information about the structure of an answer. In the paper, the solution of completing answer balances by the sum of percentage of positive answers and negative answers was proposed. This will indicates the level of certainty among respondents concerning tendency of changes in business. In the paper, the interpretation of such variable and the graphic presentation of balances and sums variables were presented
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 86, s. 206-214